Flörkeite, (K3Ca2Na)[Al8Si8O32]·12H2O: A Rare Zeolite from Pyrometamorphic Rocks of the Hatrurim Complex, Israel - Katarzyna Skrzyńska; Georgia Cametti; Irina O. Galuskina; Yevgeny Vapnik; Evgeny Galuskin (Lithosphere, 2022)
AbstractFlörkeite, a rare zeolite with PHI (phillipsite) framework type, was found in numerous amygdaloidal voids in pyrometamorphic rocks of the Hatrurim Basin, Hatrurim Complex, Israel. This is the second reported occurrence of flörkeite previously found in a Ca-rich xenolith from a quarry at the Bellerberg volcano near Ettringen, East Eifel volcanic area, Germany. The mineral with the empirical crystal chemical formula (K2.91Ca2.00Na0.91)[Al7.96Si8.04O31.94]·12H2O (P-1, no. 2, a=19.9366 2, b=14.2517 1, c=8.89350 10 Å, α=88.2480 1, β=125.0960 10, γ=89.6350 10, V=2019.19 4 Å3, and R=3.41%) did not show significant differences with respect to that of the type locality. The Raman spectrum of flörkeite is here reported for the first time. No significant differences are noticed compared to phillipsite-K. The main band ~470 cm-1, characteristic of the PHI-type structures, is independent on framework order and Si/Al ratio. The zeolite mineralization of amygdules in pyrometamorphic rocks results from meteoric water circulations in Al-rich rocks during their cooling. The crystallization sequence of zeolite corresponds to the Ca/(K+Na) ratio decrease. Flörkeite formed at the end of a low-temperature crystallization sequence, indicating the predominant role of potassium in crystallization. The occurrence of flörkeite in different pyrometamorphic rocks implies the relatively uniform, regional mineral-forming conditions, and open hydrologic system of zeolitization. In pyrometamorphic rocks of the Hatrurim Basin, the process of zeolitization is characterized by low silica activity and high pH conditions.